IMPOLITENESS IN POLITICAL DEBATES BY GEORGIAN POLITICAL LEADERS - Koroshinadze, Natalia (Online Journal of Humanities ETAGTSU, 2019)
The main goal of this ongoing research is to identify the ways, both linguistic (verbal) and supralinguistic (non-verbal) utilised by Georgian female political leaders when building up their identities in the process of TV debates. For this, the research relies on two theoretical sources: a genrespecific approach to political debate shows and the role of impoliteness in the process of construing the identity of the leader. Full Text (PDF)